Bluetooth message LCD display - Rameesh, Gunasekaran (2008)
The advancement in technology has driven the world towards efficient communication technologies where infrared is less used. Bluetooth is more appropriate to be used for communication because the signal will not be disrupted easily till a certain range of distance. Bluetooth message LCD display is a system that has been designed to enable user to spread news immediately from the place you are in a certain range. Many wired shout out box has been designed to spread news at workplace in common. This project acts as a wireless shout out box. With this Bluetooth Message conveyor it becomes possible to spread messages and news in a workplace for instance, which can be interconnected and transmitted using a single Microchip PIC16F877 microcontroller through a Personal Area Network (PAN). The network in this project consist a Bluetooth module and a Bluetooth dongle. This is the two wireless devise that communicate to display the message at a graphic LCD screen